Understanding Stress Coping Strategies Among Nurses Providing Care for COVID-19 Patients: A Qualitative Study - Mohammad-Rafi Bazrafshan; Zohreh Faramarzian; Fatemeh Sookhak; Esmaeil Kavi; Fatemeh Zeraatpishe; Fatemeh Mohseni (Mental Illness)
Conclusion: Knowing strategies that nurses choose to deal with stressful conditions such as the outbreak of COVID-19 can be a factor that helps healthcare institutions to provide solutions to reduce the stress of nurses. Therefore, taking effective measures to improve the working conditions of nurses will lead to providing better services to patients and thus increasing the efficiency of the healthcare system.